Physio-Chemical and Biological Characterization of Novel HPC (Hydroxypropylcellulose):HAP (Hydroxyapatite):PLA (Poly Lactic Acid) Electrospun Nanofibers as Implantable Material for Bone Regenerative Application - S., Mary Stella; T. M., Sridhar; R., Ramprasath; Jolius, Gimbun; U., Vijayalakshmi (MDPI, 2023)
The research on extracellular matrix (ECM) is new and developing area that covers cell proliferation and differentiation and ensures improved cell viability for different biomedical applications. Extracellular matrix not only maintains biological functions but also exhibits properties such as tuned or natural material degradation within a given time period, active cell binding and cellular uptake for tissue engineering applications. The principal objective of this study is classified into two categories. The first phase is optimization of various electrospinning parameters with different concentrations of HAP-HPC/PLA(hydroxyapatite-hydroxypropylcellulose/poly lactic acid). The second phase is in vitro biological evaluation of the optimized mat using MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) assay for bone regeneration applications. Conductivity and dielectric constant were optimized for the production of thin fiber and bead free nanofibrous mat. With this optimization, the mechanical strength of all compositions was found to be enhanced, of which the ratio of 70:30 hit a maximum of 9.53 MPa (megapascal). Cytotoxicity analysis was completed for all the compositions on MG63 cell lines for various durations and showed maximum cell viability on 70:30 composition for more than 48 hrs. Hence, this investigation concludes that the optimized nanofibrous mat can be deployed as an ideal material for bone regenerative applications. In vivo study confirms the HAP-HPC-PLA sample shows more cells and bone formation at 8 weeks than 4 weeks. © 2022 by the authors.